Front Cover: Similarity of anthropogenic stressors is multifaceted and scale dependent. Issue 1 (27th January 2022) - Orr, James A.; Rillig, Matthias C.; Jackson, Michelle C.
Abstract : Similarity of Stressors Ecosystem managers and environmental scientists need novel tools to understand and tame the diversity of anthropogenic stressors threatening biodiversity worldwide. In article number ntls.20210076, James Orr, Matthias Rillig and Michelle Jackson develop a scale‐dependent and multifaceted framework to assess the similarity of stressors. This work will enhance predictions of the combined effects of stressors and will be useful when managing ecosystems exposed to novel and emerging stressors.